Always Watched, Always Watching: The Role of Surveillance in Writing Educator Experiences with Generative Artificial Intelligence - Veselka, Mercedes; Lingard, Lorelei; Hibbert, Kathryn; Ott, Mary (Discourse and Writing/Rédactologie, 2025)
Generative artificial intelligence is disrupting the pedagogies of educators who teach writing. Amidst the disruption, they are grappling with who this technology is asking them to become. Drawing on Foucault’s metaphor of the prison panopticon as a surveillance mechanism, we explore how teachers are positioned by surveillance of student writing post-generative AI. This paper highlights the experiences of two educators working in distinct policy contexts. Part of a broader study (n=39) exploring how language and literacy teachers in secondary and postsecondary contexts work with, around, or against the use of AI in student writing, the focal perspectives in this paper show the tensions of remaining the teachers they want to be while constrained by their institutional contexts. In understanding how these educators both resist and take-up the role of ‘AI detective’, the findings illustrate how writing pedagogies are shaped by surveillance. The role of the AI detective not only has implications for the ways educators see themselves, but also their ways of seeing learners. This research contributes to theory and practice at the intersection of artificial intelligence, writing practices, and teacher agency, offering critical questions to empower pedagogical responses to generative AI.